2016
DOI: 10.1016/j.cell.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Cpf1 in Complex with Guide RNA and Target DNA

Abstract: Cpf1 is an RNA-guided endonuclease of a type V CRISPR-Cas system that has been recently harnessed for genome editing. Here, we report the crystal structure of Acidaminococcus sp. Cpf1 (AsCpf1) in complex with the guide RNA and its target DNA, at 2.8 Å resolution. AsCpf1 adopts a bilobed architecture, with the RNA–DNA heteroduplex bound inside the central channel. The structural comparison of AsCpf1 with Cas9, a type II CRISPR-Cas nuclease, reveals both striking similarity and major differences, thereby explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
750
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 614 publications
(776 citation statements)
references
References 41 publications
20
750
4
2
Order By: Relevance
“…The structure of the AsCpf1-crRNA-DNA ternary complex, which is similar to a recently reported structure of a closely related ternary complex [25], resembles a bilobal scaffold with an overall "Crab Claw" shape ( Figure 1C and 1D). AsCpf1 can be divided into two lobes: an α-helical recognition (REC) lobe consisting of Helical-I and Helical-II domains, and a NUC lobe consisting of OBD, LHD and RuvC domains, as well as the newly characterized Nuc domain [25] ( Figure 1A, 1C and 1D). The bridge helix motif is inserted between RuvC-I and RuvC-II motifs and connects the REC and NUC lobes from the middle of the whole complex ( Figure 1C).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…The structure of the AsCpf1-crRNA-DNA ternary complex, which is similar to a recently reported structure of a closely related ternary complex [25], resembles a bilobal scaffold with an overall "Crab Claw" shape ( Figure 1C and 1D). AsCpf1 can be divided into two lobes: an α-helical recognition (REC) lobe consisting of Helical-I and Helical-II domains, and a NUC lobe consisting of OBD, LHD and RuvC domains, as well as the newly characterized Nuc domain [25] ( Figure 1A, 1C and 1D). The bridge helix motif is inserted between RuvC-I and RuvC-II motifs and connects the REC and NUC lobes from the middle of the whole complex ( Figure 1C).…”
Section: Resultssupporting
confidence: 53%
“…By comparing the recently reported structures of pre-target-bound Cpf1-crR-NA binary complex [23] with target-bound Cpf1-crRNA-DNA ternary complex (this study; see also ref. [25]), we found that Cpf1 employs a unique mechanism for target recognition distinct from that reported for Cas9.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Distant homology searches of the putative Cas proteins were performed using HHpred from the HH-suite 49 . High scoring HHpred hits were used to infer domain architecture based on comparison to solved crystal structures 50,51 , and secondary structure that was predicted by JPred4 52 . Protein modeling was performed using Phyre2 53 .…”
Section: Crispr-cas Computation Analysesmentioning
confidence: 99%